A Survey on Energy Efficient Routing Protocols in WSN - Hemalatha, A; Sasirekha, D (International Journal of Computer Sciences and Engineering, 2025)
Wireless Sensor Networks (WSNs) consist of large number of tiny, battery powered sensor nodes with sensing, computation, and wireless communications technologies. These Nodes sense and send their reports towards a centralized node which is called ―sink or base station. This transmission and reception process consumes lots of energy as compared to data processing, all sensor nodes are processed by limited capacity battery resources which are difficult to replace or recharge due to the unsuitable nature of located nodes. Therefore, to increase the life time of the nodes in WSN, the designing of energy aware routing protocol is vital role in WSN to increase the life time of the sensor nodes. An Energy Efficient Routing is a significant issue in the designing of Wireless Sensor Network (WSN) protocols. This paper presents the list of various type of energy efficient routing protocols have been studied having classified them into proper categories.